2017
DOI: 10.3892/mmr.2017.8328
|View full text |Cite
|
Sign up to set email alerts
|

Tsoong induces apoptosis and inhibits proliferation, migration and invasion of pancreatic ductal adenocarcinoma cells

Abstract: The roots of Codonopsis cordifolioidea (classified as campanulaceae cordifolioidea), locally known as Tsoong, have been used as a tonic food. The major components isolated from Tsoong have been demonstrated to present anti-human immunodeficiency virus-1 activities and cytotoxicity against various tumor cell lines. However, the possible effects of the novel compound isolated from Tsoong, cordifoliketones A, on pancreatic ductal adenocarcinoma (PDAC) cells, are still unknown. In the present study, cordifoliketon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 31 publications
(42 reference statements)
0
11
0
Order By: Relevance
“…The tumor growth was evaluated as the mean volume± SE. At the end of experiment, the IATL-mediated apoptosis in tumors was evaluated using flow cytometry [ 19 , 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…The tumor growth was evaluated as the mean volume± SE. At the end of experiment, the IATL-mediated apoptosis in tumors was evaluated using flow cytometry [ 19 , 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…Another extract, from the roots of the plant Codonopsis bulleyana Forest ex diels (locally known as Tsoong), has been shown to display anticancer effects. This extract inhibited autophagy in cancer cells through activation of the NFκB pathway and induction of apoptosis, resulting in a dose-dependent reduction of HCT116 and SW480 colon cancer cell proliferation [ 49 , 50 ]. In addition, an oral administration of a high dose (20 g/kg) of the extract reduced the growth of SW480 tumor xenografts in mice.…”
Section: Anticancer Activity Of Codonopsis Extractsmentioning
confidence: 99%
“…Previous studies have found that Codonopsis bulleyana is a non-toxic food with multiple effects (Pinhua et al, 2015, Pinhua et al, 2013, Ruoli et al, 1999a, Ruoli et al, 1999b, Yunpeng et al, 2017, Zijun et al, 2009, Qiongfen et al, 2002, Luan et al, 2018a, Luan et al, 2018b, Qiongfen et al, 2003, Ruoli et al, 1999a, Ruoli et al, 1999b). In this experiment, we found that Codonopsis bulleyana can promote intestinal motility and improve the intestinal microbiota composition of the constipation model.…”
Section: Discussionmentioning
confidence: 99%
“…There is less research on disease treatment mechanism of Codonopsis bulleyana . Studies have shown that (Ruoli et al, 1999a, Ruoli et al, 1999b, Yunpeng et al, 2017, Zijun et al, 2009, Qiongfen et al, 2002, Luan et al, 2018a, Luan et al, 2018b, Shabi et al, 2018), Codonopsis bulleyana can improve intestinal function, regulate immune function, and enhance cardiovascular system, which can inhibit colorectal cancer in mice. Constipation can be treated by surgery, physical method, etc.…”
Section: Introductionmentioning
confidence: 99%